Monaco : Assessment of the Supervision and Regulation of the Financial Sector Volume I-Review of Financial Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report, 2003)
This review of the financial sector regulation and supervision in Monaco in the context of the offshore Financial center assessment program contains technical advice and recommendations given by the IMF in response to the authorities of Monaco's request for technical assistance. It assesses the antimoney laundering and combating the financing of terrorism (AML/CFT) regime based on the Draft IMF and Bank AML/CFT Methodology. It also evaluates the regulation of portfolio management and mutual funds relative to the International Organization of Securities Commissions (IOSCO) Objectives and Principles of Securities Regulation.